Use of lactate as the main metabolic marker to control the functional state of the body during the preparation of weightlifters - Kuznetcov, S.; Chernogorov, D.; Matveev, Y. (Journal of Physical Education and Sport, 2020)
This article presents data that show both individual and general changes in the level of lactate concentration in the blood of weightlifting athletes depending on the nature and intensity of physical activity, which confirms the possibility of using the abovementioned metabolic indicator during sports training to monitor recovery processes in the body and the effectiveness of planned activities during training cycles. The purpose of this study is to consider the state of glycolytic processes in weightlifters by determining the concentration of blood lactate in the blood using modern, more advanced, and accurate diagnostic methods; based on the obtained results, the objective is to re-evaluate the possibilities of using the indicated biochemical marker in various zones of physical activity intensity. The study involved 25 athletes (14-20 years old) with qualifications ranging from the 2nd adult category to candidates for master of sports. A modern SuperGLeasy lactometer was used. More than 300 samples were analyzed. The results of the study showed that in the samples of athletes of the 1st group [in which the average level of lactate before training was close to the physiological norm (1.22 ± 0.44 mmol/L)], when carrying out planned training loads in the intensity zone from 70% to 80%, the concentration of lactate in the blood showed a decreasing tendency (to 1.17 ± 0.38 mmol/L), which was not a statistically significant difference (p = 0.05). An increase in the blood lactate level reached a statistically significant value (2.12 ± 0.62 mmol/L, p < 0.05) only when planned training loads were performed in the limiting intensity zone (90-100%). Even higher lactate concentrations in the blood were determined in the samples of athletes in the 2nd and especially 3rd groups; in these groups, this indicator was at least 2 times higher than the physiological norm even before the start of training loads.